Effects of dysmenorrhea on work productivity and quality of life in Japanese women: A large-scale web-based cross-sectional study - Maika Nariai; Osamu Wada-Hiraike; Eri Maeda; Masayo Matsuzaki; Mayuyo Mori-Uchino; Maho Furukawa; Yuki Enomoto; Hiromi Ga; Risa Takai; Miyuki Harada; Yutaka Osuga; Yasushi Hirota (PLoS ONE, 2025)
Research question How significant is the impact of dysmenorrhea on work productivity and quality of life (QoL) among Japanese women?. Methods This large-scale cross-sectional study was conducted using a web-based self-report questionnaire administered via a smartphone application (LunaLuna). The Work Productivity and Activity Impairment Questionnaire: General Health (WPAI-GH) and the SF-36v2 health survey were used to assess work productivity and health-related QoL, respectively. Work productivity and health-related QoL were compared between the severe and non-severe groups as defined by the dysmenorrhea score, which assesses the severity of menstrual pain, its impact on daily activities, and medication use. A multiple regression analysis was performed to estimate the magnitude of the effect of dysmenorrhea on work productivity and health-related QoL after adjusting for confounding factors. Results In total, 2,555 women were included in the analysis. Among them, 2064 women completed the dysmenorrhea score questionnaire, and 902 (43.7%) participants with a dysmenorrhea score of ≥3 were categorized as the severe group. The median overall work impairment was 16% higher in the severe dysmenorrhea group than in the non-severe dysmenorrhea group. In the multiple regression analysis, despite adjusting for confounding factors, the severity of dysmenorrhea remained a significant predictor of impaired absenteeism; presenteeism; overall work impairment; activity impairment; and reduced physical, mental, and social QoL. Additionally, low annual household income (<5,000,000 yen) was a significant predictor of reduced work productivity and lower mental and social QoL. Conclusions The severity of dysmenorrhea significantly affects the work productivity and quality of life of Japanese women. A dysmenorrhea score of ≥3 as a threshold for treatment eligibility may be a useful and potentially valid criterion. The application of a dysmenorrhea score may facilitate the screening of dysmenorrhea in clinical practice.